SOSIALISASI PERSIAPAN WAWANCARA DAN PROFESIONALISME BAGI PENCARI KERJA DALAM MENDUKUNG PENCAPAIAN SDGs MELALUI PROGRAM KOLABORASI - Ary Priambodo; Annisa Syafira Efrial; Debora Justice Valentina (Jurnal Nusantara Mengabdi, 2026)
Purpose: This community service program aimed to enhance career readiness among high school and university graduates by improving their understanding of labor market dynamics, employability skills, and the utilization of the SIAPkerjaID platform provided by the Ministry of Manpower of the Republic of Indonesia.Research Methodology: The program was implemented through socialization sessions, interactive discussions, job interview simulations, and practical demonstrations involving members of the Alumni Association of SMA Negeri 4 Jakarta (Himals 4 Jakarta). Participants received training on curriculum vitae preparation, interview strategies, workplace professionalism, and the use of SIAPkerjaID for employment-related services.Results: The program improved participants’ understanding of recruitment processes, interview objectives, workplace competencies, and the use of SIAPkerjaID. Interview simulations strengthened participants’ communication, problem-solving, self-awareness, resilience, and collaboration skills. The findings also revealed that many participants possessed relevant competencies but experienced difficulties in effectively communicating their strengths during recruitment.Conclusions: Integrating interview training, employability skills development, and digital employment platforms can strengthen career readiness while supporting SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 10 (Reduced Inequalities).Limitations: The program was limited to participants attending the activity and did not evaluate long-term employment outcomes.Contributions: This study highlights the value of integrating employment literacy, interview training, and digital employment platforms in community-based career preparation programs.